Exploring School Climate and Teacher Self-Efficacy in Indonesian Senior High School - Wahyu Sri Ambar Arum; Sri Nuraini; Eliana Sari (International Journal of Pedagogy and Teacher Education, 2023)
School climate and teacher self-efficacy were correlated with research areas on physical, physiological, and personal and collective beliefs. Quantitatively, prior studies have reported positive results on students' performance. However, scant evidence in the school climate body of literature explored from a qualitative perspective to describe why and how teacher self-efficacy contributes to a positive school climate beyond students’ performance. Therefore, this study explores school climate and teacher self-efficacy in an Indonesian senior high school. Moreover, this study approached Yin’s (2018) case study with qualitative design. The case was one of an urban school with the school’s paradigm and policy to integrate technology into the teaching process to face the entertainment industry. Eight teachers were recruited from four subjects (e.g., Bahasa Indonesia, Physical, Social, and Biology). The data were collected through observations and interviews, and we employed thematic analysis. Our study shows that 1) physical school climate with sufficient school facilities and technology supported the development of good school climate that facilitated teachers to seek feedback and reflection; 2) teachers' self-feedback and peer evaluative feedback became a point of departure for teachers' engagement with teachers’ sources of self-efficacy that affected their development of teaching performance and strategy. Theoretical and practical implications of school climate and teacher self-efficacy will also be discussed.